The Anti-Orpheus: Queering Myth in Ducastel et Martineau’s Théo et Hugo dans le même bateau (Paris 05:59) - Todd W. Reeser (Studies in 20th & 21st Century Literature, 2018)
Olivier Ducastel and Jacques Martineau’s 2016 film Théo et Hugo dans le même bateau (Paris 05:59: Théo & Hugo) concludes on an Orphic note, inviting a consideration of the entire film as based on the myth of Orpheus and Eurydice. The film appropriates but also radically transforms elements of the foundational myth—including especially Orpheus’s turn to pederasty in Ovid’s Latin version—crafting a queer love story based on potentiality out of the tragedy of the heterosexual love story. In so doing, the film channels Herbert Marcuse’s idea of Orphic refusal in Eros and Civilization, opening up the myth to reconfigure Orphic constructs of gender and sexuality for utopian ends.
Keywords: Orpheus; Ducastel; Martineau; queer film; French film; Eurydice; Marcuse; myth; underworld; HIV; homosexuality; myth in pop culture